Effect of the Thickness of Insulator Polymeric Films on the Memory Behavior: The Case of the Polymethylmethacrylate and the Polystyrene - J. A. Avila-Niño; A. O. Sustaita; M. Reyes-Reyes; R. López-Sandoval (Journal of Nanotechnology)
The effect of thickness variation on the memory behavior of the polymethylmethacrylate-(PMMA)-based devices has been investigated. The PMMA film thicknesses have been varied between 5 to 300 nm, and we have found that the film thickness determines the type of behavior: ohmic, write-once-read-many-times (WORM) memory with two ON states, WORM memory with a negative differential resistance (NDR) region, and WORM memory without NDR region. The fact that similar results were obtained using different solvents to dilute PMMA (chlorobenzene, chloroform, and dimethyl sulfoxide), as well as using an other insulating polymer such as polystyrene (PS), leads to the conclusion that the phenomenon of memory depends on the aluminum electrodes, organic film thickness, and the compliance current used during the electroformation whereas the type of organic layer (PMMA or PS) has minor influence. From here, we conclude that the conductivity switching of the insulator organic film is due to the injection of aluminum particles into the film during the first voltage cycle.